Long-Term Unemployment in Poland in 2008-2012 - Tendencies, Structure and Selected Determinants - Kucharski, Leszek (Olsztyn Economic Journal, 2013)
This study presents the structure and tendencies in long-term unemployment in Poland in the years 2008-2012. This study identifies the groups of people with an increased risk of long-term unemployment. The analyses produced the following conclusions. The groups with the highest risk of long-term unemployment include: singles, people aged of 55 and above and people with a low level of education. Young people with university and general secondary education faced the lowest risk of long-term unemployment.